2020
DOI: 10.1108/ijpcc-07-2020-0083
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the impact of COVID-19 on over-the-top media platforms in India

Abstract: Purpose The outbreak of COVID-19 saw a robust increase in viewership of over-the-top (OTT) media platforms. This study aims to investigate the impact of COVID-19 on OTT platforms in India, as it has led to reshaping consumer content preferences. Design/methodology/approach The authors have conducted primary research by doing a survey and focus group discussion. The first study has focused on the impact of various factors such as time, content, convenience, satisfaction and work from home (WFH) on OTT platfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 4 publications
0
37
0
1
Order By: Relevance
“…However, there was also an increase in the use of technology for entertainment. For example, there has been an increase in users and streaming hours on services such as Netflix and Spotify ( Madnani et al., 2020 ). Another change in consumer purchasing behavior regarded the physical point of sale.…”
Section: Systematization Of the Relevant Literaturementioning
confidence: 99%
“…However, there was also an increase in the use of technology for entertainment. For example, there has been an increase in users and streaming hours on services such as Netflix and Spotify ( Madnani et al., 2020 ). Another change in consumer purchasing behavior regarded the physical point of sale.…”
Section: Systematization Of the Relevant Literaturementioning
confidence: 99%
“…Chang and Meyerhoefer (2020), Dannenberg et al (2020), and Bounie et al (2020) found that online retail shopping replaced the traditional shopping channels, especially in food products such as groceries, fruits, and vegetables. Madnani et al (2020), Blasco et al (2020), Sunitha and Sudha (2020), and Cellini et al ( 2020) studied the impact of the crisis on media consumption and found that digital media consumption increased during and after the lockdown, time and money spend on OTT platforms increased drastically. Digital consumption surpassed television and newspaper consumption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…She focuses on the role of Lana, a non-human sensor featured in the show as a reflection of a physical distancing warrant during the COVID-19 crisis. Madnani et al (2020) prove the impact of the pandemic on reshaping consumer content preferences, Nhamo et al (2020) describe the influence of the coronavirus on the leisure, gaming, and entertainment industries (including the issue of suspending production on film sets), while Dixit et al (2020) or Ebner and Greenberg (2020) study the binge-watching phenomenon during these times.…”
Section: The Pandemic and The Vod Sector: MM Perspective Includedmentioning
confidence: 99%